The voice of people’s perspective on the future of health resilience post pandemic hits: A numerically scaled survey in 19 provinces in Indonesia - Nurlaila Ika; Amalya Dewi Meta (E3S Web of Conferences)
For a very long time, Indonesia’s health resilience has struggled with a shortage of sufficient demographic statistics. This will impede the creation of practical plans for allocating resources wisely and assessing public health initiatives. In order to address the present and upcoming health concerns, expanding databases on previous pandemics is essential. The purpose of this study is to investigate the perspective of Indonesians regarding previous pandemics that have impacted the country’s health security. This study was conducted using a cross-sectional design. An overall total of 224 Indonesian people from 19 provinces completed a numerically scaled survey. According to our one-way ANOVA with Games-Howell’s multiple comparisons for the ten variables under observation, people tended to position themselves in fully supporting forms as both self- and government-trusting. On the other hand, they were against ignorance and pessimism towards the government’s handling of the pandemic. Instead, they favoured acting on their own free will to defend themselves without making needless motions. Overall, our data show that people are optimistic and confident in health resilience at the national level because they are aware of how to manage pandemics, and they have faith in the government to handle health crises.